IMPLEMENTATION OF CONTEXTUAL LEARNING ASSISTED BY PAMADI MEDIA ON BAR CHART TOPICS TO TRAIN DATA PRESENTATION AND ANALYSIS SKILL AMONG FIFTH-GRADE ELEMENTARY SCHOOL STUDENTS - Aulia Canzabella Ayustasari Kusuma Putri; Candra Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to present and analyze data is a crucial competency in elementary school mathematics, particulary regarding bar charts. This study employed a quantitative approach with a descriptive quantitative design, involving 27 fifth-grade elementary school students. Data were collected through assessments of student worksheets (LKPD), a bar chart evaluation test, and observation sheets tracking student activity during lesson. Research instruments included rubrics for data presentation and analysis skills, evaluation questions, and student activity observation sheets. Data were analyzed using descriptive statistics, specifically mean scores, learning mastery percentages, and student activity percentages. The result indicate that contextual learning supported by PAMADI media effectively fosters data presentation and analysis skills among fifth-grade students. This approach has the potential to help students understand data as information derived from real-life situations within the school environment—specifically through activities such as data collection, tallying, creating bar charts, and drawing simple conclusions from the data. These findings are expected to offer an alternative approach to mathematics instruction that is more concrete, contextual, and focused on developing data literacy among elementary school students.